The effect and safety of small-molecule antiviral drugs on long prognosis of post-COVID-19 pulmonary fibrosis: a real-world study in China - Xu, Yilin; Lu, Ming; Li, Yawei; Den, Xiaoling; Peng, Dechang; Zhou, Fuqing; Li, Anqi; Hou, Tieying; Xiang, Tianxin (Frontiers in Microbiology, 2026)
BackgroundPost-COVID-19 pulmonary fibrosis (PCPF) is one of the most common diagnoses after COVID-19 acute infection. However, the interventions for long-term prognosis of PCPF are relatively lacking.AimWe aimed to observe one-year readmission and mortality rates among patients with PCPF, and tried to explore the impact of small-molecule antiviral drugs (SMADs) during hospitalization on the prognosis.MethodA total of 372 patients diagnosed as PCPF were enrolled. 293 of them treated with SMADs and the remaining 79 treated with NO SMADs. One-year readmission and mortality rates were evaluated via regression analysis.ResultsDuring hospitalization, 16 of the 372 patients died. An additional 19 survivors died within one-year postdischarge. Among survivors, 49.62% were readmitted. Compared to the NO-SMAD group, the SMAD group presented a lower one-year readmission rate (45.97%vs. 63.64%, p = 0.020) and a reduced risk of one-year readmission (HR = 0.65, 95% CI: 0.44 to 0.96, p = 0.030).ConclusionNearly half of PCPF patients experienced readmission within one-year following their initial hospitalization for acute COVID-19. Importantly, treatment with SMADs during the acute infection phase was significantly associated with a reduced readmission rate.